2018
DOI: 10.3390/app8112049
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Technique and Properties of Nano-TiO2 Photocatalytic Coatings for Asphalt Pavement

Abstract: According to the characteristics of asphalt pavement, a kind of nano-TiO2 photocatalytic coating was prepared by using the emulsified asphalt as the carrier. All of its properties met the technical requirements. An exhaust gas degradation test device and its test steps were developed. The evaluation indexes, cumulative degradation rate, and degradation efficiency, were put forward. From the two aspects of the nano-TiO2 content in photocatalytic coatings and the spraying amount of photocatalytic coatings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In order to obtain photocatalytic asphalt mixtures, it is possible to highlight four main techniques that can be utilized to apply the semiconductor materials in the asphalt mixtures: (i) spraying coating [6,9,39,45,67,70,72], (ii) volume incorporation [6,67,72,76], (iii) bitumen modification [70], and (iv) spreading [67,72,77,78]. Bitumen modification is developed before the manufacture of the asphalt mixture.…”
Section: Materials and Techniques For Application Of Photocatalytic Ementioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain photocatalytic asphalt mixtures, it is possible to highlight four main techniques that can be utilized to apply the semiconductor materials in the asphalt mixtures: (i) spraying coating [6,9,39,45,67,70,72], (ii) volume incorporation [6,67,72,76], (iii) bitumen modification [70], and (iv) spreading [67,72,77,78]. Bitumen modification is developed before the manufacture of the asphalt mixture.…”
Section: Materials and Techniques For Application Of Photocatalytic Ementioning
confidence: 99%
“…Wang et al [78] concluded that the friction and texture depth of the asphalt mixtures decreased when the spreading TiO 2 coverage rate (by emulsion spreading) is increased. Considering the local technical requirements, 550 g/m 2 is the maximum coverage rate that respects these parameters.…”
Section: Mechanical and Surface Impacts And Design Of Photocatalytic mentioning
confidence: 99%
“…From 2000 to 2010, only two studies were conducted in which TiO 2 photocatalysts were mixed with concrete and cement [ 31 , 32 ]. However, seven studies were conducted from 2010 to 2020 [ 29 , 33 , 34 , 35 , 36 , 37 , 38 ]. These studies mainly focused on road pavement materials, exterior materials, and roof finishing materials.…”
Section: Introductionmentioning
confidence: 99%
“…A review of previous studies on the application of TiO 2 is presented below. The most representative applications are cement road materials, which include pavement blocks [ 29 ], asphalt pavement [ 33 , 36 , 37 ], and mortar [ 34 , 35 ]. The reduction in NO x concentration was examined by adding TiO 2 photocatalysts to these cement road materials, and it was observed that the NO x concentration can be reduced by up to 60–80% [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation